Young children's transfer of learning from a touchscreen device. (March 2016) - Huber, Brittany; Tarasuik, Joanne; Antoniou, Mariana N.; Garrett, Chelsee; Bowe, Steven J.; Kaufman, Jordy; ,
Abstract: Because young children are devoting increasing time to playing on handheld touchscreen devices, understanding children's ability to learn from this activity is important. Through two experiments we examined the ability of 4- to 6-year-old children to learn how to solve a problem (Tower of Hanoi) on a touchscreen device and subsequently apply this learning in their interactions with physical objects. The results were that participants demonstrated significant improvement at solving the task irrespective of the modality (touchscreen vs. physical version) with which they practiced. Moreover, children's learning on the touchscreen smoothly transferred to a subsequent attempt on the physical version. We conclude that, at least with respect to certain activities, children are quite capable of transferring learning from touchscreen devices. This result highlights the limitations of generalizing across screen-based activities (e.g., "screen time") in discussing the effects of media on young children's development. Highlights: Children (4- to 6-years-old) learned to solve a problem on a touchscreen device. Children's learning from the touchscreen was readily applied to the physical world. Touchscreen-based learning did not require prior experience with a similar 3D puzzle.